2019
DOI: 10.1080/02650487.2019.1607649
|View full text |Cite
|
Sign up to set email alerts
|

Text versus pictures in advertising: effects of psychological distance and product type

Abstract: The authors examine effects of marketing messages that use text or pictures for advertising durable or nondurable products appealing to consumers' perceptions of close versus far psychological distance. In three studies, ads featuring text (pictures) evoke more favorable attitudes and purchase intentions toward products to be purchased in the distant (close) future or at a distant (close) location. In addition, ads featuring text (pictures) evoke more favorable attitudes and purchase intentions for durable (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
(39 reference statements)
1
22
0
2
Order By: Relevance
“…The findings contribute to understandings of how colours play key roles in advertising effectiveness. The results align with the match‐up hypothesis (Baek & Yoon, 2017; Choi, Yoon, Kim, & Kim, 2019; Till & Busler, 2000), which predicts that endorsements are more effective when advertising components such as spokesperson and ad messages are thematically consistent. Consequently, when consumers visually process the colour green and semantically process the word green, the colour harmonizes with the message and evokes psychological congruency.…”
Section: Discussionsupporting
confidence: 80%
“…The findings contribute to understandings of how colours play key roles in advertising effectiveness. The results align with the match‐up hypothesis (Baek & Yoon, 2017; Choi, Yoon, Kim, & Kim, 2019; Till & Busler, 2000), which predicts that endorsements are more effective when advertising components such as spokesperson and ad messages are thematically consistent. Consequently, when consumers visually process the colour green and semantically process the word green, the colour harmonizes with the message and evokes psychological congruency.…”
Section: Discussionsupporting
confidence: 80%
“…Empirical evidence is consistentpictures are more persuasive for proximal consumption events, while text is preferable for distant consumption events (Choi et al, 2019;Lee et al, 2009). Using advertisements of fruit and furniture, Choi et al (2019) found that pictures evoke more favorable attitudes to the brand and purchase intention for non-durable goods for immediate consumption (fruit) but that textual-based advertisements elicit more favorable responses for durable goods where psychological distance is greater (furniture). While there is an absence of previous studies comparing textual and pictorial PoS materials, based on CLT and related empirical evidence for fruit advertisements it is assumed that: H3.…”
Section: Theorymentioning
confidence: 92%
“…Consequently, pictures should match psychologically close objects and text congruent with psychologically distant ones (Trope et al, 2007). Empirical evidence is consistentpictures are more persuasive for proximal consumption events, while text is preferable for distant consumption events (Choi et al, 2019;Lee et al, 2009). Using advertisements of fruit and furniture, Choi et al (2019) found that pictures evoke more favorable attitudes to the brand and purchase intention for non-durable goods for immediate consumption (fruit) but that textual-based advertisements elicit more favorable responses for durable goods where psychological distance is greater (furniture).…”
Section: Theorymentioning
confidence: 96%
“…La CLT suggère un ensemble d'opérationnalisations perceptuelles, conceptuelles et sensorielles 4 pour guider l'entreprise dans l'adaptation de sa communication selon que le consommateur expérimente une distance psychologique forte ou faible. Pour les techniques perceptuelles, lorsque le consommateur est en situation d'éloignement (vs. proximité), l'entreprise peut améliorer ses réponses en utilisant davantage de texte plutôt que d'images (Amit et al, 2009(Amit et al, , 2013(Amit et al, , 2019Choi et al, 2019 ;Torrez et al, 2019 ;Yan et al, 2016) ou en présentant la publicité en noir et blanc plutôt qu'en couleurs (Lee et al, 2017 ;Stillman et al, 2020 ;Wang et al, 2020). Elle peut également jouer sur le niveau d'horizon de la publicité en proposant un horizon bas (vs. haut) lorsque le consommateur est en condition d'éloignement (vs. proximité) (Roose et al, 2019).…”
Section: La Distance Psychologique Comme Variable Clé Pour Décrypter Les Phénomènes De Digitalisation De La Consommationunclassified
“…Pour les techniques perceptuelles, lorsque le consommateur est en situation d’éloignement ( vs . proximité), l’entreprise peut améliorer ses réponses en utilisant davantage de texte plutôt que d’images (Amit et al, 2009 ; 2013 ; 2019 ; Choi et al, 2019 ; Torrez et al, 2019 ; Yan et al, 2016) ou en présentant la publicité en noir et blanc plutôt qu’en couleurs (Lee et al, 2017 ; Stillman et al, 2020 ; Wang et al, 2020). Elle peut également jouer sur le niveau d’horizon de la publicité en proposant un horizon bas ( vs .…”
Section: La Distance Psychologique Pour éClairer Le Comportement Du Consommateurunclassified